2019
DOI: 10.1080/19404476.2019.1565508
|View full text |Cite
|
Sign up to set email alerts
|

What Do Middle Grades Preservice Teachers Believe about Writing and Writing Instruction?

Abstract: After third grade, students' motivation and enjoyment of writing begins to wane, and this trend continues through most of their education. Middle grade students especially need high-quality writing instruction; however, many teachers report feeling inadequately prepared to teach writing. To combat these issues, teacher preparation programs should understand how their preservice teachers feel about writing and teaching writing. The present study surveyed 150 middle grade preservice teachers to determine their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…The role of literature in developing students' writing skills is very essential. The students can acquire enjoyment during the online learning process in which it can help students to decrease their stress (Hodges et al, 2019). The use of other creative writing strategies is recommended to assess students' writing skills such as essay writing, poetry writing, or novel writing (Göçen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The role of literature in developing students' writing skills is very essential. The students can acquire enjoyment during the online learning process in which it can help students to decrease their stress (Hodges et al, 2019). The use of other creative writing strategies is recommended to assess students' writing skills such as essay writing, poetry writing, or novel writing (Göçen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this ability of dyslexic students is not taken into account by teachers. Research has shown that students with dyslexia are gifted in 3D models [12,57], and if teachers use 3D images, 3D maps, and 3D simulations, dyslexic students may develop better understanding of the subject and improve geographical skills important for their life like orientation, decoding map symbols, and so on. Despite the fact that 55.7% of geography teachers had an ICT certification, and 65.6% of teachers believe enough or very much that the school's technological equipment is satisfactory, it is interesting that the majority of them do not actually use it.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to do this, they first should be interested in the subject they teach, and in this particular case we refer to the subject of geography. According to Hodges et al [57], teachers with negative attitudes spend little time discussing and teaching science topics in their classroom, rely more on standardized methods and low-level teaching, and are less trained. As a result, they are less able to motivate their students toward the subject they teach [29].…”
Section: Discussionmentioning
confidence: 99%
“…The first principle is represented by the writing content presented throughout the professional development. To maximize the content, the focus was on instruction, strategies, standards, and assessment (Frey et al, 2016; Graham, 2018; Graham et al, 2002, 2012, 2016; Harris et al, 2013; Hodges, Wright, & McTigue, 2019; Shanahan & Shanahan, 2008; Serravallo, 2017; Tompkins, 2019; Wright, 2016). I also integrated writing theories and application (Hodges, 2017; Hodges & McTigue, 2014; Hodges & Weber, 2015).…”
Section: The Write Principlesmentioning
confidence: 99%